NATIONAL POSITION STATEMENT: A PROPOSAL ON OPERATIONAL PRINCIPLES AND PROCESS. - Yu, S. C. (The Accounting Review, 1959)
Abstract The indispensableness of a national position statement in addition to the national income accounting system for macroeconomic analysis can scarcely be overemphasized. But this hardly seems to be recognized by most economists who seem to have placed greater emphasis on income accounts than on stock accounts. Indeed, students of economics have failed to visualize the vantage of combining position and income statements in their analytical work. It is clear that to use but one of the two statements to analyze an economy is at best a partial study. Moreover, the macroaccounting mechanism will become an incomplete system without a balance sheet. In the application of accounting to economics it should be pointed out that the national balance sheet alone cannot furnish all the information needed for national position analysis. For a penetrating study a combination with other branches of macroaccounting seems desirable, such as regional and sector balance sheets, national income accounts, input-output tables, moneyflows, and balance of payments. In order to explore fully the functions of national position statement, a series of statements covering a period of several years will give a more meaningful study than the use of any single statement.